Commentary on Mari Romarheim Haugen: Investigating Periodic Body Motions as a Tacit Reference Structure in Norwegian Telespringar Performance - Swijghuisen Reigersberg, Muriel (Empirical Musicology Review, 2017)
This study investigates periodic body motion (foot-tapping and vertical hip motions) as a reference structure in a specific style of traditional Norwegian dance music called telespringar. The intimate relationship between music and motion is often highlighted in rhythm studies of telespringar, so this study encompasses both sound and motion analyses. It is based on a motion capture study of three telespringar performers, examining the foot-stamping of one fiddler and vertical hip motions of two dancers. The results indicate that rather than being primarily derived from the sound itself, the underlying rhythmic structures in telespringar depend upon a shared and embodied knowledge of the underlying asymmetrical reference structure that is implicit in the production and perception of telespringar. I explore here how the methodology used by the author might be further justified and explored. I will also propose ways in which the article could be made more accessible to researchers who question the universality of research outcomes arrived at using laboratory-based experimental settings.